(untitled) (Central Asian Journal of Medical Sciences, 2017)
Objectives: To determine chemical composition and antioxidant activity of poll gland secretions. Methods: Physical and chemical constituents, such as moisture and ash content, were determined using standard methods, crude fat was determined using the Soxhlet method, and organic composition was analyzed using GC-MS. Macro- and micro- element contents were determined using ICP-OES. Protein concentration was determined using the Bradford assay, and protein profiles were determined using SDS-PAGE. Antioxidant activity was determined using the DPPH free-radical scavenging technique. Results: Camel poll gland secretions contained 23 minerals. Potassium (89030 mg/kg) was most predominant, followed by calcium (12955 mg/kg), iron (8546 g/kg), aluminum (6105 mg/kg), magnesium (4563 mg/kg), sodium (2452 mg/kg), and zinc (14198 mg/kg). Total protein content was 11.7%. SDS-PAGE analysis of poll gland secretions revealed the presence of three different protein bands with the molecular weights of 35kDa, 68kDa and 130.5kDa. 12 organic compounds were determined by GC-MS in the poll gland secretions. Antioxidant activity of poll gland secretions was IC 50-176.2 µg/ ml. Conclusion: Proteins with the molecular weights of 35kDa, 68kDa, and 130.5kDa were determined in poll gland secretions, and they displayed potent antioxidant activity.